A late embryogenesis abundant protein HVA1 regulated by an inducible promoter enhances root growth and abiotic stress tolerance in rice without yield penalty. Issue 1 (9th September 2014) - Chen, Yi‐Shih; Lo, Shuen‐Fang; Sun, Peng‐Kai; Lu, Chung‐An; Ho, Tuan‐Hua D.; Yu, Su‐May
Summary Regulation of root architecture is essential for maintaining plant growth under adverse environment. A synthetic abscisic acid (ABA)/stress‐inducible promoter was designed to control the expression of a late embryogenesis abundant protein (HVA1) in transgenic rice. The background of HVA1 is low but highly inducible by ABA, salt, dehydration and cold. HVA1 was highly accumulated in root apical meristem (RAM) and lateral root primordia (LRP) after ABA/stress treatments, leading to enhanced root system expansion. Water‐use efficiency (WUE) and biomass also increased in transgenic rice, likely due to the maintenance of normal cell functions and metabolic activities conferred by HVA1 which is capable of stabilizing proteins, under osmotic stress. HVA1 promotes lateral root (LR) initiation, elongation and emergence and primary root (PR) elongation via an auxin‐dependent process, particularly by intensifying asymmetrical accumulation of auxin in LRP founder cells and RAM, even under ABA/stress‐suppressive conditions. We demonstrate a successful application of an inducible promoter in regulating the spatial and temporal expression of HVA1 for improving root architecture and multiple stress tolerance without yield penalty.